My Life and My Efforts - May, Karl, 1842-1912; Olesch, Gunther (Salt Lake City, UT : Project Gutenberg, 2001)
"My Life and My Efforts" by Karl May is an autobiography written in the early 20th century. This work reflects on the author$1 (Bs tumultuous life experiences, focusing on themes of personal struggle, redemption, and the quest for truth. It provides insights into May$1 (Bs formative years, including his relationships and the social context of his upbringing. At the start of the autobiography, Karl May introduces readers to his philosophical perspective through an allegorical tale about the lands of Ardistan and Jinnistan, representing selfishness and virtue, respectively. He recounts his childhood experiences growing up in poverty, detailing the hardships faced by his family and the complicated dynamics with his parents, particularly his father's violent temper. The narrative shifts between reflective commentary and personal anecdotes, illustrating May's growth and the influence of his grandmother, a significant figure in his early life who shaped his understanding of love and morality. The opening portion highlights May$1 (Bs introspective nature, as he grapples with the difficult truths of his past while striving for a greater understanding of his identity and purpose. (This is an automatically generated summary.)s
Translation of Mein Leben und Streben.
Release date is 2001-08-01
Keywords: May, Karl Friedrich, 1842-1912; Authors, German -- 19th century -- Biography